A commitment and call to strengthen and expand qualitative research efforts to improve the impact of antimicrobial stewardship. Issue 4 (1st October 2021) - van den Bergh, Dena; Brink, Adrian
Abstract: Inadequate recognition of the value of qualitative research in healthcare, notably in antimicrobial stewardship (AMS), in addition to a lack of publishing space in medical journals has prompted JAC-Antimicrobial Resistance to focus on a qualitative series of AMS papers to incite interest in and support for pivotal qualitative approaches that make an indispensable contribution to our understanding of antibiotic use and how to address antimicrobial resistance. In this series, invited authors with diverse backgrounds and considerable expertise address and review intricate and varying qualitative research methods, behaviour change determinants, interventions and qualitative perspectives, with the aim of strengthening commitment and expanding qualitative initiatives to further the impact of AMS globally.